Fashion dalam Pandangan Islam dan Kristen - Ainun, Ainun; Rambe, Uqbatul Khoir; Utomo, Wahyu Wiji (ANWARUL, 2024)
This research examines fashion from Islamic and Christian views. The methodology used in this research is qualitative with a library research research design. And the data sources obtained from this research are primary and secondary data sources that are in accordance with the discussion. Then this research uses a phenomenological approach method, where the phenomenological approach method is an approach that attempts to capture various problems that exist in society. Meanwhile, the theoretical approach is a comparative-descriptive theory. This research aims to explore how religion regulates its people in fashion, especially clothing, and also to find out whether there are similarities and differences in clothing in Islam and Christianity. Based on this research, the results showed that dressing in Islam and Christianity requires women to dress to cover their bodies and requires women to wear clothing appropriate for women. In Islam, there is more emphasis on dressing to cover the private parts, the clothes worn are thick and loose, not tasyabbuh, not required to wear fragrance/perfume, not glamorous clothes and not as jewelry. And the essence of clothing for Muslim women is to cover their private parts, not for the purpose of showing off and arrogance which will have a bad impact on themselves. Christianity emphasizes on its followers to dress appropriately and fulfill the requirements stated in the Bible.